Studi Teologis Kata “Pikirkanlah Perkara Yang Di Atas” Menurut Kolose 3:1-3 Dan Aplikasinya Bagi Orang Percaya - Paulus Kunto Baskoro; Yonatan Alex Arifianto (Institut Agama Kristen Negeri Toraja, 2022)
This paper aims to find the practical theological meaning contained in Colossians 3:1-3 regarding